The First Neolithic Occupation of La Cova del Randero (Pedreguer, Alicante, Spain) - Roca de Togores Muñoz Consuelo (De Gruyter, 2021)
The excavations at “Cova del Randero” (Pedreguer, Alicante, Spain) began in 2007 within the programme of archaeological interventions of the Archaeological Museum of Alicante. The cavity, located in one of the valleys that connect the coast with the inland mountains, presents a wide sequence of occupations that begins in the Upper Palaeolithic and continues throughout the different phases of the Neolithic. The results of a multidisciplinary study, carried out in an archaeological context associated with the first Neolithic presence of the cavity, are presented here. This occupation is defined by a unique combustion structure to which a set of artefacts and biofacts are linked. This archaeological context, probably of a specific nature, is related to the first agro-pastoral communities settled in the area. The fireplace is well defined stratigraphically and sedimentologically because of its reddish soil, which corresponds to hunter-gatherer occupation levels of the cavity, and under the greyish sediments that characterise the use of the cave as a fold during the Middle Neolithic. This occupation event was dated both by the associated materials, among which a fragment of cardial ceramic was found, and by radiocarbon dating of a metacarpus of Ovis aries around 5075–4910 cal BC (epicardial Early Neolithic). This data allows us to link the occupation of the cavity at this time with pastoral activity in a medium mountain environment. However, it also allows us to infer the environmental characteristics in which the first farming communities of the mountains of Alicante were developed.